A Human Rights Perspective of Assisted Suicide: Accounting for Disparate Jurisprudence. (11th September 2017) - Martin, Stevie S
Abstract: This article critically examines the decision of the New Zealand High Court in Seales v Attorney-General [2015] NZHC 1239, which rejected the claim that that country's blanket ban on assisted suicide violated various rights enshrined in the New Zealand Bill of Rights. That outcome runs contrary to the Canadian Supreme Court's decision in Carter v Canada (Attorney General) [2015] 1 SCR 331. This disparity in result arose despite overt similarities between the rights documents in each of the jurisdictions and, more significantly, notwithstanding the fact that the trial judge in Seales placed heavy reliance upon the decision in Carter . With two new challenges to the blanket ban on assisted suicide in England and Wales progressing through the lower courts, and given proposed amendments to the ban in both New Zealand and its antipodean neighbours – the Australian states of Victoria and New South Wales – it is a propitious time to consider the reasons for the disparate outcomes in Seales and Carter . This article will demonstrate that the trial judge's reasoning in Seales was wanting in a number of important respects, particularly in terms of the characterisation of the objective of the blanket ban. These limitations undermine the decision's utility as authority both domestically and internationally. This is particularly important given the high likelihood that reference will be made to the decision during debate in the New Zealand Parliament regarding amendments to the ban in that country and the possibility that the Legislatures in Victoria and New South Wales, as well as the English courts hearing the current challenges to the ban in that jurisdiction will, particularly given the shared common law background, refer to the judgment in Seales .